If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-54=2(y+6)
We simplify the equation to the form, which is simple to understand
-54=2(y+6)
Reorder the terms in parentheses
-54=+(+2y+12)
Remove unnecessary parentheses
-54=+2y+12
We move all terms containing y to the left and all other terms to the right.
-2y=+12+54
We simplify left and right side of the equation.
-2y=+66
We divide both sides of the equation by -02 to get y.
y=-33
| 9(t-4)+6t=5(3t+4)-13 | | 9x-42=x-15 | | p^4-k^4=0 | | 5(4x-6)=-90 | | 4sp^4-4sk^4=0 | | -(7y+4)-(-6y-5)=0 | | 6(-2x-3)=-102 | | X-7.8=-6.9 | | 3(2x+7)=-9 | | 4=4+y | | -4(2x-6)=5x+24-7x | | 0=4+y | | 9i^22= | | -r+16r=-15 | | 27v^3+64=0 | | .50x=9 | | 12p-9p-p=16 | | y=4(-3)-3 | | 20k-15k+-k+2=10 | | -2=.25a-13 | | 2k+4k-1=17 | | 2x^2-12x-3=0 | | y+31=16 | | -3(x-1)=7 | | 19+x=51 | | -2(-4x-5)=42 | | 10x^2+7x-12= | | w^2+8w-15=0 | | 4x-7=4(x-2)-2 | | x^4-13x^2+12=0 | | 7-(w-4)+2(w-3)=6w-5 | | 5x-18=5x-18 |